CT analysis of left ventricular function predicts short term survival in patients following transcatheter aortic valve implantation: 1-year outcome data. (3rd October 2022) - Ijgua, M; Arnold, M; Eckstein, M; Smolka, S; Bittner, D; Ammon, F; Kondruweit, M; Moshage, M; Achenbach, S; Marwan, M
Abstract: Introduction: Contrast-enhanced cardiac CT routinely performed prior to transcatheter aortic valve implantation (TAVI), allows assessment of cardiac morphology and function. We assessed left ventricular function in CT as a predictor of survival following TAVI. Methods: 500 consecutive patients referred for CT assessment of aortic root anatomy prior to TAVI were screened for inclusion in this analysis. All CT data sets were acquired using a third-generation dual source system. For assessment of aortic root anatomy, acquisitions were acquired using ECG-gated retrospective spiral acquisition and multiphase reconstructions in 10% increments of the cardiac cycle were rendered (slice thickness 0.75, increment 0.4 mm). left ventricular endocardial contours were automatically traced by a dedicated software (syngo. via, Siemens Healthineers, Forchheim, Germany) throughout the cardiac cycle and manually adjusted if required. Global left ventricular function parameters (end-diastolic and end-systolic volumes, stroke volume, cardiac output and ejection fraction) were derived by volumetric assessment. Results: Out of 500 patients, 439 patients (mean age 80±6 years, 56% males, and Log EuroScore 23±14%) were included in this analysis (61 patients were excluded due to poor CT image quality or missing outcome data). Previous cardiac surgery had been performed in 15% of the patients, 50% had obstructive CAD with previous interventional or surgical revascularisation and 18% had a previous acute coronary syndrome. One-year survival was 83% (366/439 patients). Parameters of left ventricular function were as follows: mean LVEDV 172±56 ml, mean LVESV 78±62 ml, mean LV ejection fraction 59±18%, mean LV stroke volume index 51±22 ml/m 2, mean LV cardiac output 6.6±3.3 L/min and LV cardiac index 3.5±1.7 l/min/m 2 . Cluster analysis of multiple LV-function surrogate parameters identified a group of patients with higher 1-year mortality, with LVEF identified as a predictor of 1-year survival with a cut-0ff of ≥37% associated with an OR 0f 0.52 (95% CI 0.27 to 0.98). Conclusion: Assessment of left ventricular function using functional CT data sets is feasible and allows risk stratification of patients following TAVI. Among LV functional parameters, CT derived LV-ejection fraction with a cut-off ≥37% identifies patients with better short-term outcome. Funding Acknowledgement: Type of funding sources: None.